Customer Satisfaction Analysis Using Package and Document Delivery Services Pt. Indonesian Post (Case Study of Makassar Central Post Office) - Nasyirah Nurdin; Nurfaisyah Aladin; Mujahid Mujahid (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Customer satisfaction is one thing that has an important role in business. Customer satisfaction is a major milestone in the success of a company. This study aims to determine customer satisfaction using package & document delivery services PT. Indonesian Post. This research is a qualitative study with a qualitative descriptive analysis approach using informants from users of PT. Indonesian Post. This research data was collected through library research techniques and field research using interviews and observations. The results show that customer satisfaction occurs when consumers get services according to expectations, such as responsive service, affordable prices, and the accuracy of shipment estimates are the reasons why consumers are satisfied and loyal to use PT. Indonesian Post.